Treatment outcome of doxorubicin versus idarubicin in adult acute myeloid leukemia. (2021) - Sherif, Hemat Afifi; Magdy, Ahmed; Elshesheni, Heba Anees; Ramadan, Sherein Mahmoud; Rashed, Reham A.
Abstract: Purpose: The present study aimed to compare treatment outcome of idarubicin versus doxorubicin in combination with Ara-C as induction therapy for untreated AML patients. Patients and methods: This retrospective study included 143 patients with de novo AML. All patients received full dose of standard induction therapy (3 + 7) using anthracyclines (doxorubicin or idarubicin) and cytarabine. Results: The studied groups had comparable CR. No significant differences were noted between the studied groups regarding DFS and OS. The DXR group had significantly lower cost in comparison to IDA group. Conclusions: Idarubicin doesn't have a clear advantage over doxorubicin in treatment of AML.